Effect of diet energy content and level of restriction on performance, nutrient digestibility, and puberty in replacement beef heifers - Brandt, Robert T., Jr.; Pope, Ronald V.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty Angus × Hereford crossbred weanling heifers (548 lb) were used in a 2×2 factorial experiment to evaluate dietary energy concentration (NEg .51 vs .61 Mcal/lb) and intake restriction (to produce 1.25 and 2.0 lb/d gain). Intake of the diets (corn - corn silage based; 14% CP) was adjusted every 2 weeks. Steer counterparts to the heifers were used in a 2×3 factorially arranged digestion experiment using the same treatments with an additional ad libitum intake level. There were no interactions between energy content and level of restriction. Heifers fed the higher energy diet maintained equal daily gain on 9.7% less (P<.004) feed, the probable result of higher (P<.0001) OM digestibility. Feed efficiency was improved 6.3% (P=.14) for heifers fed the higher energy diet. NRC (1984) energy equations underpredicted rate of gain of 1.25 and 2.0 lb/d by 24.6 and 7.7%, respectively, probably as a result of enhanced (P<.05) nutrient digestibility at the more restricted intake. Puberty (based on serum progesterone) was not influenced by treatment. Limit-feeding grain to produce replacement heifers appears practical when harvested forages are scarce and(or) high-priced.
Keywords: Beef; Beef heifers; Feed restriction; Nutrient digestibility; Performance